Editional Tasks of Publishing the Correspondence of F. M. Dostoevsky: Source Problem - Alekseeva, Lyubov (Neizvestnyj Dostoevskij, 2024)
The researchers of F. M. Dostoevsky’s epistolary heritage recognize the historical value of correspondence as a reliable source that helps build a genuine biography of the writer. Dostoevsky’s letters are not only a biographical source, especially since the writer did not keep a diary and did not leave memoirs, but also a part of the writer’s literary heritage. The tradition of publishing Dostoevsky’s letters has a long, 140-year history. Since the 1880s different types of letter publications have been implemented: individual publications, as part of collections and complete works, and in scientific articles. Currently, the researchers have published and commented on all known Dostoevsky’s letters preserved in autographs. Over time, scientists also realized the value of letters from correspondents addressed to the writer. Commented publications of individual letters, thematic groups and epistolary cycles of correspondence appeared. The researchers faced the task of systematizing all letters and preparing a commented publication of a unified set of Dostoevsky’s correspondence. In Russian editional practice, a tradition has developed of publishing the correspondence of the 19th-century classics, an example is the correspondence of A. S. Pushkin, which has been reprinted more than once. Despite the experience with this kind of publication, the epistolary heritage of such an outstanding 19th-century classic as Dostoevsky has not been published in the form of a complete set of correspondence, including letters from correspondents. Its preparation poses various many questions for researchers. The article identifies the editional tasks that arise in the process of publishing correspondence, and proposes possible ways to solve them. The work on the publication of Dostoevsky’s entire creative heritage in the language of the 19th century is carried out as part of the publication of his Complete Works in the author’s spelling and punctuation. In part, these tasks were implemented through electronic publication of letters from Dostoevsky and his correspondents on the website of Petrozavodsk State University Philolog.ru. At the moment, it contains most of the letters, which are verified by handwritten autographs. In the future, a scientifically commented set of correspondence is slated for publication. Electronic publication allows to offer a variable and multi-level representation of Dostoevsky’s epistolary, thereby solving many editional problems.